EDUKASI DENGAN MEDIA LEAFLET TERHADAP POSISI DAN PELEKATAN PADA BAYI SAAT MENYUSU - Aswita Amir; sitti ria rowa; Nur Islamiyah (Media Gizi Pangan, 2020)
Exclusive breastfeeding is a baby who is only breastfeeding without any other liquid such as formula milk, orange, tea, mineral water, and without any additional solid food such as banana, porridge, biscuits, and rice Tim up to 6 months from first birth except drugs and supplements. The cause of mothers who do not breastfeed their children is assumed due to the lack of understanding about the right position and well sticking during breastfeeding. This research aims to determine the effect of leaflet media education on the position and sticking during breastfeeding. This research is a kind of pre-experimental research by applying pre-test and post-test design to the subject of the research, and data analysis used a Wilcoxon statistical test. The sample of this research is the mother who had a baby aged 0-5 months. Moreover, there was 25 sample of this research. The data were obtained by using an interview and questionnaire. While the researcher used direct observation to the mothers who do not breastfeed their baby, then the mother was given an education using a counseling method about leaflet media for three days and 1 day for evaluation. The data were presented in tables, graphs, and descriptive form. The result of the research performed that 100% of babies who had the wrong position before being educated, well sticking (53.1%), wrong sticking(94.7%). On the other hand, after being educated, the sample knows the right position of breastfeeding and get 100%, and well sticking (100%). The result of the statistical test showed that there is a correlation (p=0.000) between before giving the leaflet education and after giving the leaflet education.